Ice and mineral licks used by caribou in winter - Heard, Douglas C.; Williams, T. Mark (Rangifer, 1990)
In winter, barren-ground caribou obtain minerals from ice and soil licks. Between December and April we have seen caribou cratering on the surface of frozen lakes and licking the ice. Ice samples from eight licks on four lakes contained concentrations of calcium, magnesium, sodium, potassium, phosphorus, chloride and sulphate many times higher than in the surrounding unlicked ice or than would be expected in lake water. Soil licks being used in March and June had high concentrations of calcium, magnesium, sodium phosphorus and potassium. In winter caribou may be seeking supplements of all of the major mineral elements (calcium, magnesium, sodium and potassium) at ice and soil licks because lichens, their staple winter diet, are low in minerals and may also reduce the absorption of some minerals.